Polimerisasi Ester Dari Asam Lemak Sawit Distilat (ALSD) Menggunakan Inisiator benzoil Peroksida 0,3 % - Herry Novriansyah; Ahmad Fadli; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm Fatty Acid distillate (PFAD) as a byproduct the processing of palm oil has great potential to be used as raw material oil-based polymers. The aims of this research to study the process polymerization of ester from PFAD using initiator (benzoyl peroxide) 0.3%. Stage of the process consists of three stages. The esterification stage was done at temperatur70° C, reaction time of 120 minutes, reactant ratio 1: 8 (PFAD: methanol), concentration of catalyst (H2SO4) 1% (w/w) PFAD; polymerization stage was done at temperature 120, 130,and 140°C, concentration of initiator (benzoyl peroxide) 0.3% (w/w) and variation of polymerization reaction time 3, 4, and 5 hours, and polyesterification stage was done at temperature 175-200 °C, ratio of reactants 1: 1 (polymerized methyl ester: ethylene glycol), and the reaction time of 4 hours. The results of polymerization was analyzed by using viscosity test, FT-IR (Fourier Transform Infra Red) and GCMS (Gas Chromatography Mass Spectrometry). The highest viscosity was 32,97 mPa.s at temperature 140°C and 4 hours. Theresult using FT-IR showed that the polymerization process was unsuccessful, this was indicated by the presence of the vinyl group. The result of GCMS showed there had been molecular weight addition in polymerization process, that was only three times the initial molecular weight.Keywords: benzoyl peroxide, esterification, palm fatty acid distillate, polymerization